THE INFLUENCE OF ENTREPRENEURSHIP EDUCATION AND SOCIAL MEDIA ON STUDENT’S ENTREPRENEURIAL INTENTIONS - Karina Putri Syahrani; Marsofiyati; Purwana, Dedi (Faculty of Economics and Business, Universitas Negeri Jakarta, 2023)
Entrepreneurship is one of the alternative ways to overcome unemployment. For this reason, it is necessary to have entrepreneurship education and the use of social media in order to increase entrepreneurial intentions in the younger generation. This study aims to examine entrepreneurship education, social media and entrepreneurial intentions, as well as to determine the direct and indirect influence between entrepreneurship education and social media on entrepreneurial intentions. The research method used in this study is a quantitative method. The data is sourced primary data. Data collection is carried out by survey. Questionnaire items are distributed online through Google Forms with a scoring scale using a likert scale. The affordable population in this study was 143 students. The sampling technique used is purposive sampling. The number of samples collected was 100 students determined by the Isaac & Michael table. The data was processed using SPSS software version 23 by conducting correlation tests and multiple regression analysis. The results of this study show that entrepreneurship education and social media have a positive impact on entrepreneurial intentions both partially and simultaneously.